The Analysis of Pandanus Leaf (Pandanus Amarylifolius Raxb) as A Plant-Based Pesticides for Adult Phase Fruit Fly (Bactrocera Sp) - Rusmiati Rusmiati; Sri Mardojo (Humanistic Network for Science and Technology (HNST), 2018)
Fruit flies (Bactrocera Sp) has been known as the main pest to the fruits commodity in Indonesia which caused large economic loss. Pandanus leaf (Pandanus Amarylifolius Raxb) already examined that it was contained some chemical componds that have potential to control pests. The purpose of this research was to analyze the effect of pandanus leaf (Pandanus Amarylifolius Raxb) extract to the mortality of adult phase fruit flies (Bactrocera Sp). The research was done by using laboratory experiment with true experimental post test only controlled group design. The result would be observed only after the animal test exposed by pandanus leaf extraxt with concentration variation was 5%, 10%, 15%, 20%, and 25%. Several test also have done in this research such as photochemistry test, spektrofotometer test, and fruit flies (Bactrocera Sp) mortality. The result showed that pandanus leaf (Pandanus Amarylifolius Raxb) extract contain active compound such as flavonoid, essential oil, tanin, saponin, and alkanoid. Statistic result using anova test showed that p value < 0.05 which mean there were a significant difference of fruit flies mortality in each concentrate of pandanus extract and there were significant influence of pandanus extract to the fruit flies (Bactrocera Sp) mortality. Probit results then, showed that LC50 of pandanus leaf (Pandanus Amarylifolius Raxb) extract to fruit flies (Bactrocera Sp) was 5.216%. Keywords: Fruit flies(Bactrocera sp), Pandanus leaf extract (Pandanus amaryllifolius Roxb.), Insecticide